Responsive disassembly of nucleic acid nanocomplex in cells for precision medicine. (August 2021) - Han, Jinpeng; Cui, Yuchen; Li, Feng; Gu, Zi; Yang, Dayong
Highlights: Controlling assembly/disassembly of nanomaterials in cells is of importance for precision medicine. Therapeutic polyphenols regulate the assembly/disassembly of biomimetic siRNA nanocomplex in cells. In cells, spatiotemporally controllable disassembly of nanocomplex is achieved in lysosomes and cytoplasm. The disassembly process triggers the complete release of drugs and siRNA that are structural components of nanocomplex. Graphical Abstract: Tannic acid (TA), a therapeutic natural polyphenol is utilized to regulate the assembly/disassembly of nucleic acid nanocomplex in cells for smart drug delivery and gene therapy. Intracellularly, spatiotemporally controllable disassembly of nanocomplex is achieved. The lysosomal acidic microenvironment specifically induces the disassembly of nanocomplex to release TA and branched-DNA/RNA. RNase H in cytoplasm specifically triggers the disassembly of branched-DNA/RNA to release siRNA. ga1 Abstract: Controlling the assembly/disassembly of nanomaterials in cells is of great importance for precision medicine. Recently, natural polyphenols served as drugs have gained considerable attentions for the treatment of cardiovascular diseases, bacterial infections and cancers. Herein, tannic acid (TA), a therapeutic natural polyphenol is utilized to regulate the assembly/disassembly of nucleic acid nanocomplex in cells for smart drug delivery and gene therapy. TA mediates the co-assembly of branched-DNA/RNA and cell membranes to form nanocomplex driven by strong affinity between TA and nucleic acids/membrane proteins. The nanocomplex is able to effectively bind to target cells, and demonstrates prolonged blood circulation and reduced macrophage clearance. Intracellularly, spatiotemporally controllable disassembly of nanocomplex is achieved. The lysosomal acidic microenvironment specifically induces the disassembly of nanocomplex to release TA and branched-DNA/RNA. RNase H in cytoplasm specifically triggers the disassembly of branched-DNA/RNA to release siRNA. Using in vitro and in vivo models, the efficacy of synergetic RNAi/chemo-therapy has been demonstrated, wherein TA promotes cancer cell apoptosis and RNAi-mediated gene silencing is enhanced. This work demonstrates that rationally designed DNA nanomaterials achieve controlled disassembly of functional moieties in cells for precision medicine.